2013
DOI: 10.2464/jilm.63.279
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanical properties of Mg^|^ndash;Ca and Mg^|^ndash;Ca^|^ndash;Zr alloys

Abstract: Cast Mg-Ca and Mg-Ca-Zr alloys were prepared from elemental metals, Mg-5Ca, and Mg-33Zr master alloys. The microstructure was examined and tensile tests performed. The microstructures of the cast Mg-Ca alloys consist of primary α-Mg dendrites and a degenerated lamellar eutectic. An addition of zirconium transformed coarse primary α-Mg dendrites to fine globular grains of approximately 20 35 μm in diameter. Hardness increased for both Mg-Ca and Mg-Ca-Zr alloys with calcium contents, and there was a slope change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Experimentally, there is some support for our model. Recent experimental studies have indeed found that Ca solutes enhance non-basal slip deformation (H. Somekawa, private communication) although they make the fracture toughness weaker as a result from the grain boundary segregation 30 , and that Zr solutes improve the elongation to failure with a positive effect on grain refinement 31 32 in which multiple slip plays an important role.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, there is some support for our model. Recent experimental studies have indeed found that Ca solutes enhance non-basal slip deformation (H. Somekawa, private communication) although they make the fracture toughness weaker as a result from the grain boundary segregation 30 , and that Zr solutes improve the elongation to failure with a positive effect on grain refinement 31 32 in which multiple slip plays an important role.…”
Section: Resultsmentioning
confidence: 99%
“…6 , this binding is dissipated over a distance of roughly 3/2 c . Using the binding energy per unit length, and the estimate of the interaction distance, one can estimate the pinning strength of an assumed immobile single Y atom 30 31 32 (this calculation is presented in the Supplementary Information .). Incorporating this pinning strength into simple models for obstacle controlled glide, we estimate that Y levels of 1 at.-% will increase the yield stress of the basal glide plane by approximately 90 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…Provided that Ca concentrations are kept below the solubility limit to avoid Mg 2 Ca formation, the corrosion rate will not sharply accelerate, while solid solutions of Mg-Ca can display appreciable ductility. [103][104][105] Copper (Cu)…”
Section: Calcium (Ca)mentioning
confidence: 99%
“…However, in excess amounts, Zr aggregates into particles larger than 5 µm and reduces the corrosion resistance of Mg alloys [26]. The casting Mg-Ca-Zr alloy has better tensile strength and elongation than Mg-Ca alloy at all Ca content ratios [27]. Heat treatment is important for Mg alloys in application.…”
Section: Introductionmentioning
confidence: 99%